Comparison of Homogeneous and Non-Homogeneous Onedimensional Heat Equation - Muhammad Arif Hannan Mohamed; Muhammad Aniq Qayyum Mohamad Sukry; Faizzuddin Jamaluddin; Ahmad Danial Hidayatullah Badrolhisam; Norazlina Subani (Universiti Sains Islam Malaysia, 2024)
Junior Researcher International Conference (iJURECON) Kolej Genius Insan (KGI) 17 dan 18 November 2020 Pages : 16-24